INFLUENCE OF DRIP IRRIGATION ON GROWTH AND YIELD OF COD X WCT COCONUT (COCOS NUCIFERA L.) HYBRID - R. Dhanapal; H. P. Maheswarappa; P. Subramanian; Ajay Kumar Upadhyay (International Coconut Community Journal, 2003)
A field experiment on drip irrigation for Chowghat Orange Dwarf X West Coast Tall (COD X WCT) coconut hybrid was conducted in laterite soil at Central Plantation Crops Research Institute, Kasaragod (Kerala, India) to study the drip irrigation requirement and its influence on growth and yield. The treatments included were three levels of drip irrigation (at 33, 66 and 100% E0 daily), basin irrigation (100% E0) and rainfed control. The experimental results revealed that annual leaf production and leaf nutrient status of coconut palm was significantly higher in the irrigated treatments compared to the rainfed control. The female flower production and nut yield with 66 per cent of Eo was on par with 100 per cent of Eo through drip and 100 per cent of Eo through basin irrigation and significantly superior compared to drip irrigation at 33 per cent of E0 and rainfed control. Drip irrigation equal to 66 per cent of open pan evaporation (Eo) proved to be the economically efficient method of irrigation with water saving of 34 per cent compared to 100 per cent of Eo through basin and drip method.